Rancang Bangun Sistem Pemanen Energi di Lantai Menggunakan Modul BQ25570 pada Aplikasi Piezoelectric Energy Harvesting - Rifki Abi Setiawan; Syaiful Alam; Umi Murdika; Sumadi Sumadi (Rekayasa, 2020)
Energy harvesting is a process whereby energy produced is derived from an external. As for external sources consisting of sunlight, sound, the wind, vibrations, the press, and others. One potential that could be used the style press derived from a footrest man while walking. The device that can be used to harvest energy by using the style press is piezoelectric. Piezoelectric is a material when given style tap hence will generate electricity. But, electricity produced piezoelectric is a signal impulse so it needs a coherent rectifier and devices series of electronic another so that the energy harvested can be stored on a battery, in this research using a module BQ25570. Module BQ25570 is an electronic device in which there are DC-DC converter, charging battery and protection, and super capacitor as media temporary storage. The research was conducted by making a prototype with size 80 cm × 50 cm, use piezoelectric kind of PZT as many as 50 strung together in parallel. Testing conducted by using the style press from the average weight of a human body. The results of tests carried out the power produced at the time of heavy 42 kg is 1,345 mW, 52 kg is 2,251 mW, 67 kg is 4,729 mW, 70 kg is 10,646 mW,  and 82 kg is 17,218 mW.